2011
DOI: 10.2753/mtp1069-6679190401
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Key Routes to Customer Delight

Abstract: Recent empirical research has shown the benefits for the service firm of providing customer delight. With this link established, it is now important to garner a greater understanding of the drivers of customer delight from the customer's perspective. In response, this research addresses three focal issues: (1) evaluating the types of employee behaviors in a service encounter that lead to delight, (2) assessing consumers' expectations prior to their delightful encounter, and (3) ascertaining the differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 54 publications
(73 reference statements)
7
78
0
Order By: Relevance
“…The significant path loading (β = 0.296, p < 0.001) suggested the significant influence of service quality on customer delight, supporting H 2 . The path loadings from satisfaction to customer delight were also significant β = 0.507, respectively; p< 0.001), providing support for H 4 .…”
Section: Resultsmentioning
confidence: 79%
“…The significant path loading (β = 0.296, p < 0.001) suggested the significant influence of service quality on customer delight, supporting H 2 . The path loadings from satisfaction to customer delight were also significant β = 0.507, respectively; p< 0.001), providing support for H 4 .…”
Section: Resultsmentioning
confidence: 79%
“…According to Finn (2005), surprising and positive levels of performance can delight customers. Many researchers have provided evidence showing that consumers experience delight in response to unexpected and surprising experiences, and that satisfying consumers largely involves meeting their expectations (Barnes et al 2011, Oliver et al 1997. For example, users usually have expectations before using an app.…”
Section: Delightmentioning
confidence: 98%
“…Customer delight in a service context has mostly been found to be created through an employee's engagement in interpersonal and extra-role behaviors (Menon/Dubé 2000;Verma 2003;Johnston 2004;Arnold et al 2005;Barnes et al 2011). Transferring these findings to the context at hand, it is suggested that by engaging in voluntary extra-role behaviors, customers, too, are able to create a source of delight with their behaviors.…”
Section: Customer Delight As a Consequence Of Positive Customer Engagmentioning
confidence: 90%
“…In-role behaviors, in contrast, are perceived as a source of delightful service experiences only from an employee perspective (Barnes et al 2013). Yet, as suggested by Barnes et al (2011), while a customer's pre-service expectations mainly involve cognitive factors such as specific employee skills, post-service evaluations critical to a customer's future behavior mostly touch upon affective experiences throughout the service encounter (p. 361). Affective experiences, by this means, are assumed to not only allow companies to emotionally connect with the customers but also to sustainably impact future customer behaviors and relationships.…”
Section: Drivers Of Customer Delightmentioning
confidence: 99%